100 artists 100 years : Alumni of The School of the Art Institute of Chicago : Centennial Exhibition - Kuh, Katharine; The Art Institute of Chicago (Chicago : The Art Institute of Chicago, 1979)
Adams, Pat ; Albert, Calvin ; Albright, Ivan ; Anderson, Lennart ; Andrews, Benny ; Baranik, Rudolf ; Barnard, George Grey ; Barnes, Robert ; Baum, Don ; Beal, Jack ; Bennett, Rainey ; Benton, Thomas Hart ; Berdich, Vera ; Bergman, Robert ; Biederman, Charles ; Bohrod, Aaron ; Booth, Cameron ; Bowman, Ken ; Brown, Roger ; Buehr, George ; Campoli, Cosmo ; Chamberlain, John ; Chapin, Francis ; Clark, Alson Skinner ; Coen, Eleanor ; Cohen, George ; Curry, John Steuart ; etc.
100 artists 100 years : Alumni of The School of the Art Institute of Chicago : Centennial Exhibition, The Art Institute of Chicago, November 23, 1979 through January 20, 1980
boek